2005
DOI: 10.1159/000087242
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Potential Cardiotoxic Side Effects of Mitoxantrone in Patients with Multiple Sclerosis

Abstract: Previous studies showed that mitoxantrone can reduce disability progression in patients with multiple sclerosis (MS). There is, however, concern that it may cause irreversible cardiomyopathy with reduced left ventricular (LV) ejection fraction (EF) and congestive heart failure. The aim of this prospective study was to investigate cardiac side effects of mitoxantrone by repetitive cardiac monitoring in MS patients. The treatment protocol called for ten courses of a combined mitoxantrone (10 mg/m2 bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 47 publications
4
11
0
4
Order By: Relevance
“…As observed by others, 7,17 we found no association of cardiac events with sex or age; we also found no association with MS disease duration at start of treatment. None of these indicators can be regarded as helpful prognostic factors for mitoxantrone associated cardiotoxic events.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As observed by others, 7,17 we found no association of cardiac events with sex or age; we also found no association with MS disease duration at start of treatment. None of these indicators can be regarded as helpful prognostic factors for mitoxantrone associated cardiotoxic events.…”
Section: Resultssupporting
confidence: 81%
“…GEE analyses revealed no significant predictors of increased AST (figure e-1D). DISCUSSION The incidence of subclinical cardiotoxicity was higher than that reported in the phase II/III mitoxantrone clinical trials 2,4 and by some, 11,17,18 although not all, [12][13][14][15] postmarketing studies. This adverse event is considered moderate by recognized standard criteria, 16 but the potential longterm consequences are unknown.…”
Section: Resultsmentioning
confidence: 84%
“…Patients in our study did not report chest pain or palpitation, and we noted no case of HF symptoms during MTX treatment. Similar conclusions were arrived at by Zingler et al [20] who evaluated LVEF by echocardiography in 73 patients with MS and found no significant LVEF reduction during treatment. In that study group, however, 1 case of atrial fibrillation episode was noted after the second MTX dose in a patients with hypertension and previous myocardial infarction.…”
Section: Discussionsupporting
confidence: 85%
“…In one series of 73 patients, no cardiotoxicity was observed, although 2 patients receiving at least 4 doses of MX were lost to follow-up. 18 Similarly, in another Class III study of 50 prospectively assessed patients, no decrease in LVEF was seen during 2 years of therapy, although cardiac function was not assessed in 3 years of follow-up after discontinuation of MX. 19 A recent Class III study of 100 patients with aggressive RRMS receiving induction MX therapy noted asymptomatic worsening LVEF in 3 patients following MX therapy.…”
mentioning
confidence: 96%